Evaluation of Changes in Physicochemical Parameters of Rape and Soybean Oils during the Frying Process of French Fries - Maria Dymkowska-Malesa; Monika Radzymińska; Beata Erlichowska (Scientific Journal of Gdynia Maritime University)
Fats, including vegetable oils, are an important component of the diet. They not only have a high energy value, but also contain nutrients that are essential for the proper functioning of the human body. The increasing consumption of fried products affects the consumption of the oils used for a long time in the deep frying processes. Vegetable oils contain large amounts of unsaturated fatty acids, which are subject to oxidative and hydrolytic processes, while thermal polymerization can also occur in them. The aim of the study was to compare the oxidative stability of rapeseed and soybean oils while frying potato chips in them at 180°C. The study presents changes in the acid and peroxide values, as well as changes in the sensory characteristics of the oils under the influence of heating. The studies showed that rapeseed oil was characterized by greater sensitivity to oxidation compared to soybean oil. Soybean oil contained more hydrolysis products, but during the frying process their increase was similar to the products formed in rapeseed oil.